Transcriptomic investigation of the biochemical function of 7-dehydrocholesterol reductase 1 from the traditional Chinese medicinal plant Anemarrhena asphodeloides Bunge. (December 2021) - Wang, Yunpeng; Xiong, Wenbo; Chen, Yidu; Zhu, Min; Liang, Jincai; Li, Yu; Huang, Jia; Huang, Liufang; Liu, Zhongqiu; Ji, Aijia; Duan, Lixin
Abstract: Anemarrhena asphodeloides Bunge (Liliaceae) is an important Traditional Chinese Medicine herb, which contains up to 6 % total steroidal saponins (timosaponins) and has multiple pharmacological properties. However, the timosaponin biosynthetic pathway has not been extensively investigated. Here we conducted de novo transcriptome sequencing and analysis of A. asphodeloides Bunge and screened for candidate genes involved in the timosaponin biosynthetic pathway. Targeted metabolite analysis showed that timosaponins primarily accumulated in rhizomes, while phytosterols (including cholesterol) were distributed throughout various organs. Most of the identified candidate genes of the timosaponin biosynthetic pathway were also highly expressed in the rhizome, consistent with the results of metabolic analysis. Based on the transcriptome results, two candidate 7-dehydrocholesterol reductase genes were cloned and heterologously expressed in the yeast Saccharomyces cerevisiae . The purified and identified products supported that Aa7DR1 possessed Δ 7 -reduction activity in yeast and therefore may be involved in the timosaponins biosynthetic pathway in A. asphodeloides Bunge. Phylogenetic analysis showed Aa7DR1 belongs to monocotyledonous Δ 7 reductase of phytosterol biosynthesis. These data expand our understanding of timosaponin biosynthesis. Graphical abstract: Transcriptomic analysis of A.asphodeloides Bunge identified an Aa7DR1 gene potentially involved in the biosynthetic pathway of timosaponins. Image 1 Highlights: Transcriptomic analysis of two organs of Anemarrhena asphodeloides Bunge. Candidate genes involved in the biosynthetic pathway of timosaponins were screened based on transcription data. An Aa7DR1 gene was identified to possess Δ7-reduction activity in yeast.